2018
DOI: 10.1007/s10029-018-1734-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain, discomfort, quality of life and impact on sex life after open inguinal hernia mesh repair: an expertise-based randomized clinical trial comparing lightweight and heavyweight mesh

Abstract: PurposeThere is a paucity of high-quality evidence concerning mesh choice in open inguinal hernia repair. Using an expertise-based randomized clinical trial design, we aimed to evaluate the postoperative impact of two different mesh types on pain and discomfort, quality of life and sex life.MethodsIn two regional hospitals, male patients with primary inguinal hernia were randomized to one of two groups of surgeons that performed the Lichtenstein operation. One group of surgeons used a heavyweight polypropylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…The promising results in using mesh implants for other hernia types [ 27 , 28 , 29 , 30 ] have encouraged the implantation of meshes also in the treatment of parastomal hernia and for prophylactic purposes.…”
Section: Treatmentmentioning
confidence: 99%
“…The promising results in using mesh implants for other hernia types [ 27 , 28 , 29 , 30 ] have encouraged the implantation of meshes also in the treatment of parastomal hernia and for prophylactic purposes.…”
Section: Treatmentmentioning
confidence: 99%
“…This might be a triggering factor for men having a higher incidence of inguinal hernia. Regarding the relation between age and inguinal hernia, it has been found that the inguinal re-Table1: Carolinas Comfort Scale questionnaire (7).…”
Section: Discussionmentioning
confidence: 99%
“…Both the technical differences and also different meshes are evaluated concerning their impact especially on movement ability and groin pain in different studies. Rutegard et al (7) found no statistical difference between light or heavyweight polypropylene mesh patients regarding QoL scores. Sanders et al (8) reported no significant superiority of mesh fixation technologies including fibrin sealants, self-fixing meshes and NB2C glues over conventional suture fixation on postoperative quality of life.…”
Section: Introductionmentioning
confidence: 94%
“…There were several studies that reported higher recurrence rates after TEP herniorrhaphy with a lightweight mesh. 8,13,18,23 The efficacy of mesh repair to prevent recurrence is based on the strengthening of weakened native tissue by a strong mesh aponeurosis scar tissue complex, formed by inflammatory response induced by the mesh material. 25,26 The mass of the implanted material and its pore size were assumed as the main factors for the intensity of this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…7 Compared with heavyweight meshes, less foreign body feeling and chronic pain were described when a lightweight mesh was used in open inguinal hernia repair. [8][9][10][11] However, in laparoscopic inguinal hernia repair, these benefits could not be demonstrated and lack of consensus exists regarding the best mesh for these procedures. 12 In addition, increased risk of recurrence is still a concern with the use of lightweight mesh used in laparoscopic repair.…”
mentioning
confidence: 99%